Stimulation of soluble guanylyl cyclase inhibits mesangial cell proliferation and matrix accumulation in experimental glomerulonephritis - Hohenstein, Bernd; Daniel, Christoph; Wagner, Andrea; Stasch, Johannes-Peter; Hugo, Christian (American Journal of Physiology-Renal Physiology, 2005)
To date, no specific treatment is established in mesangial proliferative glomerulonephritis in humans. Specific stimulation of soluble guanylyl cyclase (sGC), an enzyme catalyzing the synthesis of cGMP from GTP, can be achieved by the novel pyrazolopyridine derivative BAY 41-2272. The effect of sGC stimulation via BAY 41-2272 on mesangial proliferation was assessed in vivo using a mesangial proliferative glomerulonephritis model in rats (anti-Thy1 model). Renal biopsies, as well as glomerular isolates, urine samples, and blood samples were compared in BAY 41-2272- and placebo-treated groups during anti-Thy1 nephritis. The sGC β1-subunit is upregulated during anti-Thy1 nephritis and mainly confined to mesangial areas by immunohistochemistry. Specific therapeutic sGC stimulation during anti-Thy1 nephritis in vivo was achieved via BAY 41-2272. treatment as demonstrated by increased glomerular cGMP levels causing inhibition of mesangial proliferation, glomerular matrix accumulation, and proteinuria compared with placebo-treated animals. sGC is tightly regulated in glomeruli during experimental glomerulonephritis. Considering its beneficial antiproliferative, antifibrotic, and antiproteinuric effect in experimental glomerulonephritis, the therapeutic stimulation of sGC could become a promising future goal in mesangial proliferative glomerulonephritis in humans. Copyright © 2005 the American Physiological Society.
Created from Fastlane, Scopus look-up
Keywords: Anti-Thy1 model; BAY 41-2272; Matrix expansion